DOES EMOTIONAL CONGRUENCE AND COMPULSIVE SEXUAL BEHAVIOR INCREASE THE RECURRENCE RISKS OF CHILD SEXUAL ABUSE? - Cahyaningrum, Anindya Endah; Margaretha, Margaretha (Jurnal Psikologi, 2020)
This research examines the influence of Emotional Congruence with Children and Compulsive Sexual Behavior towards Re-offend Prediction of Child Sexual Offenders. The research was conducted on 111 residents of correctional facilities for child sexual abuse in 5 correctional institutions in East Java, all of whom were males aged 18 to 81. The prediction of reoffending was assessed using an actuarial instrument, Static-2002 which was tested with Fleiss Kappa Inter-rater Reliability 89% (14 items). Emotional Congruence with Children was assessed by the adapted Emotional Congruence Scale of Children and Sex Questionnaire (EC-CSQ; 15 items, Î± = .88). Compulsive Sexual Behavior assessed by the Compulsive Sexual Behavior Inventory-13 (CSBI-13; 13 items, Î± = .85). The data was analyzed by using correlation and multivariate linear regression analysis. The research found that age and Compulsive Sexual Behavior, particularly Distress in Daily Functioning, significantly predicted reoffending among Child Sexual Crime Offenders (R 2 = .49). However, the inability to Control Compulsive Sexual Behavior was not predictive towards reoffending. The findings of this research are expected to provide input in the criminal justice and psychological correction-rehabilitation process for sexual offenders in Indonesia.